Proteasome activity determines pupation timing through the degradation speed of timer molecule Blimp‐1. (18th October 2018) - Aly, Hamdy; Akagi, Kazutaka; Ueda, Hitoshi
Abstract : The transcriptional repressor Blimp‐1 is a labile protein. This characteristic is key for determining pupation timing because the timing of the disappearance of Blimp‐1 affects pupation timing by regulating the expression of its target β ftz‐f1 . However, the molecular mechanisms that regulate the protein turnover of Blimp‐1 are still unclear. Here, we demonstrate that Blimp‐1 is regulated by the ubiquitin proteasome system. We show that Blimp‐1 degradation is inhibited by proteasome inhibitor MG132. Pupation timing was delayed in mutants of 26S proteasome subunits as well as FBXO11, which recruits target proteins to the 26S proteasome as a component of the SCF ubiquitin ligase complex by slowing down the degradation speed of Blimp‐1. Delay in pupation timing in the FBXO11 mutant was suppressed by the induction of βFTZ‐F1. Furthermore, fat‐body‐specific knockdown of proteasomal activity was sufficient to induce a delay in pupation timing. These results suggest that Blimp‐1 is degraded by the 26S proteasome and is recruited by FBXO11 in the fat body, which is important for determining pupation timing. Abstract : Here, we showed that contribution of 26S proteasome and E3 enzyme FBXO11 which recruit Blimp‐1 to proteasome for the identified timer system to determine pupation timing in Drosophila melanogaster . These results give important information for understanding the molecular mechanism of time determination during development of organisms.